Effect of UI/UX Designer on Front End - A Nurpalah; M S Pasha; D D Rhamdhan; Hanhan Maulana; Agis Abhi Rafdhi (International Journal of Research and Applied Technology (INJURATECH), 2021)
In this digital era, product quality cannot be separated from aesthetics, those who are responsible for the beauty of product appearance are UI/UX Design and FrontEnd. Therefore, this study aims to find out what distinguishes UI/UX from FrontEnd and the correlation between UI/UX to FrontEnd. The method that this research uses is descriptive by presenting a complete picture of a particular situation based on facts, theories, and accurate reference sources with previous research. The results show that the presence of a UI/UX Designer can affect FrontEnd in the design/development of information systems. The main influence it has is in terms of appearance being more interactive as well as attractive. Even so, the position of FrontEnd cannot be replaced by a UI/UX Designer, because it is FrontEnd here who will implement the design and ensure that the aesthetics and functionality of the system run well.